Нормативно-правовий механізм врегулювання злочинів проти людства: історико-теоретичний аспект - Торош, С. О. (Видавництво Львівської політехніки, 2015)
Розглянуто поняття злочинів проти людства, питання щодо історичних причин та обставин виникнення злочинів проти людства. Аналізується історичний та теоретико-правовий підхід до шляхів та методів розв’язання таких проблем та запобігання їм. Рассмотрено понятие преступления против человечества, вопросы об исторических причинах и обстоятельствах возникновения преступлений против человечества. Анализируется исторический и теоретико-правовой подход к путям и методам предотвращения и разрешения таких проблем. The article examines the concept of crimes against humanity, the historical causes and circumstances of crimes against humanity. Analyzes the historical and theoretical, legal approach to the ways and methods to prevent and solve such problems. Moreover, in this article we see the historical beginnings of approaches and developments of the legal mechanisms in solving such problems. This article gives theoretical overview of the legal approaches in solving one of the most important issues of existing world. Moreover, in this article we see emphasis at historical and theoretical measures that influence on preventing and solving situations related to armed conflicts inside a society. At the modern world, the reality of existence such problems become more and more highly important issue. Therefore, this article once more emphasizes the seeing of such society problems as a common problem that is the most dangerous for a peaceful life and democratic developments.
Нормативно-правовой механизм урегулирования преступлений против человечества: историко-теоретический аспект
Legal mechanism of solving crimes against humanity: historical and theoretical aspects
Keywords: держава; суспільство; злочини проти людства; безпека людства; міжнародний правопорядок; міжнародні організації; государство; общество; преступления против человечества; безопасность человечества; международный правопорядок; международные организации; state; society; crimes against humanity; human security; international order; international organizations